Changes in Native Sentence Processing Related to Bilingualism: A Systematic Review and Meta-Analysis - Román, Patricia; Gómez-Gómez, Irene (Frontiers in Psychology, 2022)
The native language changes as a result of contact with a second language, and the pattern and degree of such change depend on a variety of factors like the bilingual experience or the linguistic level. Here, we present a systematic review and meta-analysis of works that explore variations in native sentence comprehension and production by comparing monolinguals and bilinguals. Fourteen studies in the meta-analysis provided information regarding the bilingual experience and differences at the morphosyntactic level using behavioral methods. Overall, we observed that first language processing is subject to small transformations in bilinguals that occur in sentence comprehension and production. The magnitude of the changes depended on bilingual experiences, but only length of residence in an L2 setting predicted the degree of change, where a shorter length of residence was associated with larger changes. Results are discussed and related to the cognitive processes that potentially cause the transformations in the first language. The present work reveals some limitations in the field that should be addressed in future studies to better understand the mechanisms behind language attrition.